Coping with Sea-Level Rise in African Protected Areas: Priorities for Action and Adaptation Measures. (16th September 2020) - Brito, José C; Naia, Marisa
Abstract: Sea-level rise, a consequence of climate change, is progressively affecting coastal areas around the globe. In turn, protected areas are keystones for protecting coastal biodiversity and the ecosystems services ensuring sustainable livelihoods. Effective management and adaptation plans are needed to maintain ecological function and integrity. In the present article, we used a coastal digital elevation model to simulate inundation surfaces and a prioritization index for ranking management interventions in 278 coastal protected areas from 27 African countries. Of these, 15 areas and eight countries demonstrated a high need for proactive management actions because of high levels of biodiversity, international conservation relevance, and exposure to sea-level rise. From the array of management actions available, tailored solutions are being implemented according to the morphology and location of the areas. Concerted action by international, government, and local partners is required for successful protection of the areas, including implementation of adaptive plans and monitoring progress schemes.